The Contribution of Gamelan Diplomacy to Restoring Bilateral Relations Between Indonesia and New Zealand - Natasha, Cheryl; Martha, Jessica (Jurnal Hubungan Internasional, 2024)
Cultural diplomacy has gained prominence for its capacity to assist governments in achieving national interests. While Indonesia and New Zealand have collaborated in various domains, their relationship was strained due to Indonesia’s protectionist policies. In response to New Zealand’s legal actions and economic sanctions, Indonesian Ambassador Tantowi Yahya intensified “gamelan diplomacy” efforts to alleviate the tension. This study investigated the question: “What contributions has gamelan diplomacy made in mending the bilateral relations between Indonesia and New Zealand, particularly in protectionism of imported products between 2017 and 2021?” To address the question, this research employed Milton Cummings’ concept of cultural diplomacy, integrated success parameters as defined by Patricia M. Goff, and utilized Brian Hocking’s multistakeholder diplomacy framework. The research method comprised primary data collection through questionnaires administered to two New Zealand residents, supplemented by a comprehensive literature review. The study concluded that gamelan diplomacy has effectively harmonized communication frequencies, enhanced positive national branding, established credibility, and fortified interstate cooperation, thus serving as a complementary tool in achieving national objectives.